Алтай бүрдлийн Зүүн Булган массивын минералоги, петрографи, петрохимийн судалгаанд - Л.Оюунжаргал,; Л.Жаргал,; Ү.Ганбаатар,; Сод.Оюунгэрэл, (Geological Issues, 2023)
Altay complex in Mongolian Altay terrane has distinguished first Marinov et al. (1963). Intrusion bodies of Altay complex located in Western Mongolia, directing from north-west to south-east and are by gabbro, diorite and granite. Thin section for Zuun (East) Bulgan massive is showing hornblende - pyroxene gabbro-diabase, biotite granite, leucogranite and biotite - hornblende diorite that are small to medium grained last three, respectively for I-IV facies. The genesis of this massive is S-type granite during collision. The granites have a wide compositional range, with SiO2 (68.14-77.1) increasing, relatively low TiO2 (0.21-0.68), Al2O3 (11.95-15.23), Fe(t) (1.26-4.63), MgO (0.06-1.57), CaO (0.47-2.09) and high K2O (2.96-5.14), constant P2O5 (0.04-0.22) contents. Heavy - concentrate mineralogical analysis for Zuun (East) Bulgan massive is presented high magnetite (0.01 gr), ilmenite (0.01 -2.01 gr), sphene (0.01 gr) and zircon (Fig. 7b), low anatase (Fig. 7f), apatite (Fig. 7e), pyrite (Fig. 7e), barite (Fig. 7a), monacite, rutile (Fig. 7d) and Ta-Nb mineral contents.